Kualitas Pelayanan Publik di Kelurahan Siwalankerto - Asturimo, Bima Raka; Syafi’i, Achmad; Kendry, M (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
The sub-district is the smallest government unit at the level of the village. Unlike the village, the sub-district does not have the right to regulate its territory more limitedly. According to the researcher, the basic reason that determines the quality of service in Siwalankerto Sub-District as the object of study is the low quality of service and always complained by the surrounding community such as printing KK or e-KTP because the tools do not fulfill, correction of birth certificates or deaths that are still not in the sub-district, correction still have to go to Dispenduk Capil, birth certificates or late deaths must go to Dispenduk Capil, which must go through the introduction, lack of staff in the sub-district is also just being filled, and land issues that always end in court. According to Zeithaml (1990) in Hardiansyah (2011: 41) states that service quality can be measured from 5 dimensions, namely: Tangible, Reliability, Responsiveness, Assurance, and empathy. In this research the researcher is only the search for the right source not as the resource person being studied. So researchers try to master and use tools that are used to explore research data in order to succeed optimally. The results of this study indicate that the quality of public services in the Siwalankerto sub-district has been applied to the dimensions of Tangible, Realibility, Responsiveness, Assurance and Empathy along with the indicators. This researcher also uses qualitative methods to see the natural condition of a phenomenon. Where according to researchers this approach aims to gain understanding and describe complex reality. However, there are several indicators that have not yet run according to the wishes of the community, including the inconvenience of the service area which is an old building including incomplete facilities and infrastructure, and the lack of employees in the newly completed sub-district. Keywords: service, quality, public, service theory